3D surgical guide for the resection of vestibular exostoses and mandibular torus: case report - Delgado-Piedra , Daniel Andrés (2025)
Resection of vestibular exostoses and mandibular tori as a key pre-prosthetic procedure for optimal edentulous rehabilitation. This article reports a case involving the resection of a mandibular torus and vestibular exostoses, emphasizing the use of a 3D-printed surgical guide for enhanced precision. A 49-year-old female patient diagnosed with mandibular tori and vestibular exostoses in the edentulous mandibular region underwent pre-prosthetic surgical treatment. The procedure involved the resection of the mandibular torus and vestibular exostoses, guided by virtual planning. Customized mandibular cutting guides, fabricated using acrylic resin, facilitated precise osteotomy. The use of these patient-specific surgical guides resulted in: reduced surgical time, minimally invasive approach, improved postoperative recovery, preserved mandibular symmetry and fewer surgical complications. At the six-month follow-up, a definitive prosthesis was placed, demonstrating excellent adaptation without soft tissue trauma, ulceration, or displacement. It is concluded that the application of 3D-printed surgical guides in the resection of mandibular tori and vestibular exostoses enables precise bone removal, minimizes surgical invasiveness, and optimizes prosthetic rehabilitation outcomes. This approach enhances surgical predictability, reduces morbidity, and ensures improved long-term patient satisfaction.